ceRNAshiny: An Interactive R/Shiny App for Identification and Analysis of ceRNA Regulation - Song, Yueqiang; Li, Jia; Mao, Yiming; Zhang, Xi (Frontiers in Molecular Biosciences, 2022)
The competing endogenous RNA (ceRNA) network is a newly discovered post-transcriptional regulation that controls both physiological and pathological progresses. Increasing researches have been pivoted on this theory to explore the function of novel non-coding RNAs, pseudogenes, circular RNAs, and messenger RNAs. Although there are several R packages or computational tools to analyze ceRNA networks, an urgent need for easy-to-use computational tools has still remained to identify ceRNA regulation. Besides, the conventional tools mainly were devoted to investigating ceRNAs in malignancies instead of those in neurodegenerative diseases. To fill this gap, we developed ceRNAshiny, an interactive R/Shiny application, which integrates widely used computational methods and databases to provide and visualize the construction and analysis of ceRNA network, including differential gene analysis and functional annotation. In addition, demo data in ceRNAshiny could provide the ceRNA network analyses about neurodegenerative diseases such as Parkinson’s disease. Overall, ceRNAshiny is a user-friendly application that benefits all researchers, especially those who lack an established bioinformatic pipeline and are interested in studying ceRNA networks.